SCIENTIFIC RESEARCH ON THE SS-15A SEPARATOR (Intent Research Scientific Journal, 2023)
Cotton ginning sector of great importance to the current stage of development, as well as technical and technological activities, from the harvesting of cotton to prevent raw material losses, while preserving the natural features of the high level of work the first time, and the resulting product to ensure uninterrupted supply to consumers must go. It should be noted needs, the use of technology on the basis of available technical equipment, it is important to timely adjustment and control.